IDENTIFIKASI PEMANFAATAN LIMBAH KULIT KACANG TANAH OLEH MASYARAKAT DI DESA WEA AU - Maria Faustina Enge Pasu; Yohanes Freadyanus Kasi; Delviana Vivi Bai (Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Bengkulu, 2026)
ABSTRACT Peanut shell waste is a byproduct of peanut production that is no longer utilized. However, this waste has not been optimally utilized and is generally discarded or burned, potentially causing environmental pollution. This study aims to identify the use of peanut shell waste as an alternative cattle feed in Wea Au Village. The research method used was descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The research informants consisted of 10 peanut farmers, community leaders familiar with the agricultural conditions in Wea Au Village. The results showed that peanut shell waste is generally used as organic fertilizer and is simply discarded around agricultural land or burned because it is considered to have no economic value. This situation results in the underutilization of agricultural waste. Conclusion: Peanut shell waste has not been optimally utilized because peanut shells are not utilized properly by the community, and are often simply discarded or burned. Therefore, outreach and mentoring efforts are needed to increase community awareness of the potential of peanut shell waste as organic fertilizer and livestock feed.